Innovations in a rapidly changing world - Halytsia, Ihor (My University, 2013)
Innovation has always been an integral part of the satellite and the socio-economic progress. They largely determined the direction and pace of that progress. The history of civilization can be seen in various aspects. But if we consider the history of the progress of civilization, it actually is a movement from one basis to further innovation.

Інновації завжди були невід’ємною частиною супутникового та соціально-економічного прогресу. Вони багато в чому визначили напрямок і темпи цього прогресу. Історію цивілізації можна розглядати в різних аспектах. Але якщо розглядати історію прогресу цивілізації, то насправді це рух від однієї основи до подальших інновацій.
Keywords: кафедра економіки праці та менеджменту; інтелектуальні досягнення; intellectual achievements; розвиток суспільства; social development